Timosaponin B-II ameliorates diabetic nephropathy via TXNI P, mTOR, and NF-κB signaling pathways in alloxan-induced mice - Yuan YL; Guo CR; Cui LL; Ruan SX; Zhang CF; Ji D; Yang ZL; Li F (Dove Medical Press, 2015)
Yong-Liang Yuan,1,* Chang-Run Guo,1,* Ling-Ling Cui,1 Shi-Xia Ruan,1 Chun-Feng Zhang,1 De Ji,2 Zhong-Lin Yang,1 Fei Li1 1State Key Laboratory of Natural Medicines, China Pharmaceutical University, 2College of Pharmacy, Nanjing University of Chinese Medicine, Nanjing, People’s Republic of China *These authors contributed equally to this work Background: Many synthesized drugs with clinical severe side effects have been used for diabetic nephropathy (DN) treatment. Therefore, it is urgent and necessary to identify natural and safe agents to remedy DN. Timosaponin B-II (TB-II), a major steroidal saponin constituent in Anemarrhena asphodeloides Bunge, exhibits various activities, including anti-inflammatory and hypoglycemic functions. However, the anti-DN effects and potential mechanism(s) of TB-II have not been previously reported.Purpose: To investigate the effect of TB-II on DN in alloxan-induced diabetic mice.Methods: TB-II was isolated and purified from A. asphodeloides Bunge using macroporous adsorption resin and preparative high-performance liquid chromatography. The effect of TB-II on DN was evaluated in alloxan-induced diabetic mice using an assay kit and immunohistochemical determination in vivo. The expression of mammalian target of rapamycin (mTOR), thioredoxin-interacting protein (TXNIP), and nuclear transcription factor-κB (NF-κB) signaling pathways was also measured using Western blot analysis.Results: TB-II significantly decreased the blood glucose levels and ameliorated renal histopathological injury in alloxan-induced diabetic mice. In addition, TB-II remarkably decreased the levels of renal function biochemical factors, such as kidney index, blood urea nitrogen, serum creatinine, urinary uric acid, urine creatinine, and urine protein, and it reduced lipid metabolism levels of total cholesterol and triglycerides and the levels of inflammatory cytokines interleukin-6 and tumor necrosis factor-α in alloxan-induced mice. Furthermore, TB-II inhibited the expression of mTOR, TXNIP, and NF-κB.Conclusion: The results revealed that TB-II plays an important role in DN via TXNIP, mTOR, and NF-κB signaling pathways. Overall, TB-II exhibited a prominently ameliorative effect on alloxan-induced DN. Keywords: Anemarrhena asphodeloides Bunge, timosaponin B-II, diabetic nephropathy, TXNIP, mTOR, NF-κB